Genetic and Environmental Contributions to the Expression of Handedness in Chimpanzees (Pan troglodytes) - Hopkins, William D. (2013)
Most humans are right-handed and, like many behavioral traits, there is good evidence that genetic factors play a role in handedness. Many researchers have argued that nonhuman animal limb or hand preferences are not under genetic control but instead are determined by random, non-genetic factors. We used quantitative genetic analyses to estimate the genetic and environmental contributions to three measures of chimpanzee handedness. Results revealed significant population-level handedness for two of the three measures --- the tube task and manual gestures. Furthermore, significant additive genetic effects for the direction and strength of handedness were found for all three measures, with some modulation due to early social rearing experiences. These findings challenge historical and contemporary views of the mechanisms underlying handedness in nonhuman animals.